Gejala PTSD (Post Traumatic Stress Disorder) Akibat Bencana Banjir pada Masyarakat Kelurahan Meranti Rumbai Pesisir Pekanbaru - Fitry Erlin; Icu Yuanda Sari (Universitas Riau, 2020)
Post-traumatic stress disorder or PTSD is an anxiety disorder that develops through exposure to a traumatic event, stressful situations, severe torture, and natural or catastrophic disasters due to human negligence. These disorders could be include 3 main symptoms, namely the feeling of re-experiencing, the desire to avoid all stimuli associated with traumatic events (avoidance), and increased awareness of the arousal, which is experienced over a period of a month or more . This study aims to find a description of the symptoms of PTSD (Post Traumatic Stress Disorder) due to flooding on Meranti Pandak Village RT 02 RW 012 Rumbai Pesisir District of Pekanbaru. Types of quantitative research and descriptive design. The study was conducted on 16 June - 01 July 2019 in Meranti Pandak Village, Rumbai Pesisir District with 45 respondents. Data collection techniques using a questionnaire. This study shows that from 45 respondents studied there were symptoms of repeated experiences 27 people (60.0%) experienced, avoidance symptoms 37 people (82.2%) experienced, negative symptoms of change 10 people (22.2%) experienced, symptoms of stimulation changes 34 people (75.6%) experienced, who experienced all the symptoms of PTSD 3 people (6.7%), so it can be concluded that found the symptoms of PTSD (Post Traumatic Stress Disorder) due to flooding It is expected that health workers provide health education and conduct ongoing evaluations to people affected by symptoms.